Investigation of the effect of magnet thickness on motor losses of PM BLDC machines using parametric approach method - Ocak, Cemi̇l; Bayindir, Ramazan; Topaloğlu, İsmai̇l (IEEE, 2011)
In this study, 500 Watts PM BLDC has been investigated using parametric approach method for determining the effect of magnet thickness on motor losses. Copper, iron losses and efficiency variation with magnet thickness calculated and represented graphically. The best performance/efficiency ratio determined versus magnet thickness. 24 slot, 4 pole and inner rotor configuration PM BLDC motor investigated.
Keywords: 7. Clean energy